Premature Ovarian Failure - Çetinkaya, M.; Kökçü, A. (My University, 2002)
Premature ovarian failure can recognize with elevated gonadotropin levels, hipoesrogenism, presence of vasomotor symptoms and amenorrhea with at least 4 months before the age of 40. Prevalence of ovarian failure is about 1% among reproductive age women and the exact etiology is unknown in most cases. Several etiological reasons may involve in presenting of ovarian failure. Ovarian failure may be the consequence of more than one abnormal condition. There are two important theories to explain ovarian failure. The first is follicular depletion and the second is dysfunction of the follicular unit response. Chromosomal abnormalities, immunologic and metabolic disorders are counted as in the other main causal factors. Also, radiotherapy and chemotherapy may cause premature ovarian failure. Especially the effect of radiation is dependent upon age and x-ray dose. This must be taken into the consideration in the treatment of malign disorders. There is no effective therapy for ovarian failure but oral contraceptives can prevent follicular depletion preventing development of folliculogenesis depending on age and the follicular reserve in radiation therapy. Oocyte donation is an alternative choice for these patients who desire fertility.
Prematür Over Yetersizliği